PELATIHAN PEMBUATAN SABUN PADAT DAN CAIR BERBAHAN EKSTRAK RIMPANG TEMULAWAK DAN SAMBILOTO PADA IBU-IBU PKK DESA MAMBANG, SELEMADEG TIMUR, TABANAN - I.G.A. Artini; A.W. Indrayani; N.W.S. Dewi; I.W. Sumardika; I.G.M.G.S.C. Trapika; I.M. Jawi; B.K. Satriyasa; I.G.M. Aman; A.N. Mahendra; I.A.A. Widhiartini; D.K. Ernawati; N.W. Tianing; N.L. Suriani; I.G. Wiranatha (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Temulawak is one of medicinal plants which possess antibacterial activity against two major causes of infection in acne namely Staphylococcus epidermidis and Propionibacterium acnes. The active compounds of temulawak are curcumin and xanthorrhizol essential oil, which possess antibacterial activity as antiseptic and antibiotic. Sambiloto (known as Andrographis paniculate), contains active compound andrographolide, which is also assumed to possess antibacterial activity. This community program was the implementation of our research for community wellbeing, which aimed to raise the knowledge and skill of PKK women at Mambang village, Selemadeg Timur, Tabanan especially in producing liquid and solid soap from natural substances (temulawak and sambiloto extract). The program was conducted by visiting our partner company PT Bali Tangi and training for liquid and solid soap production from temulawak and sambiloto (as one form of temulawak and sambiloto utilization for skin health especially for acne management). We assess participant knowledge improvement by using questionaire before and after conducting the activity. There was an improvement in participant knowledge regarding the production of soap from natural substances (temulawak and sambiloto). In conclusion, this program had increase the knowledge and skill of PKK women at Mambang village regarding liquid and solid soap production from natural substances. Keywords: antiacne, liquid soap, sambiloto, solid soap, temulawak